Relative age effect on competitive performance in judo athletes - Eduardo Victor Ramalho Lucena; Pedro Pinheiro Paes; Gustavo Augusto Fernandes Correia; Bruna Giovana Correia Souza; Mayllane Pereira da Silva Sousa; Hugo Alvares Lira (Revista da Educação Física)
The difference of chronological age in an age group is called Relative Age (RA) and its consequences on the performance of athletes is called Relative Age Effect (RAE). It is believed that the RAE among young athletes can affect their competitive success in many ways, even into adulthood. Thus, the objective of the present study was to investigate the EIR in all judo competitors of the national competitions of the year 2013, making the differentiation by age categories and the competitive performance. This study included 862 male athletes and 637 female athletes. The chi-square was used to compare the observed and expected values among quartiles, adopting significance as p < 0.05. A post hoc Bonferroni analysis was used to identify where the significant differences were (adjusted p < 0.00417). The results showed a significant difference in the male sub-15 categories (Q2 in G1: OV= 17, EV = 9.7, p = 0.001) and male sub-23 (Q1 in G3: OV= 37, EV = 10.1; p < 0.0001). In conclusion, the RAE was only identified in male athletes. However, there was great discrepancy between athletes born in the first semester and athletes born in the second semester.